The Integration of Transformational Leadership and Organizational Culture in Enhancing the Quality of Teachers’ Human Resources at Madrasah Ibtidaiyah (International Journal of Education and Literature, 2025)
The improvement of Islamic elementary education quality largely depends on the competence of teachers as the primary agents of learning. In the context of Madrasah Ibtidaiyah (MI), the challenges of globalization and the implementation of the Merdeka Curriculum demand teachers to develop professionally, innovatively, and with strong Islamic values. This study aims to analyze the integration of transformational leadership and organizational culture in enhancing the quality of teachers’ human resources in MI. A qualitative approach with a case study design was employed at three Islamic elementary schools in Central Java. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model with source and method triangulation for validation. The findings reveal that transformational leadership practiced by school principals plays a crucial role in building teachers’ motivation, commitment, and change orientation through exemplary behavior, inspiration, and empowerment. Meanwhile, an organizational culture rooted in Islamic values strengthens collaboration, professionalism, and shared responsibility among teachers. The integration of these two elements creates a synergistic effect that enhances teachers’ pedagogical, professional, and spiritual competencies. It can be concluded that transformational leadership combined with a strong organizational culture serves as an effective strategy to sustainably improve teacher quality in Madrasah Ibtidaiyah..